Undoing Gender in Indonesian Beauty Brand Dear Me Beauty Instagram Post - Ningsih, Ana Widia; Tallapessy, Albert; Hari Murti, Ghanesya (MOZAIK HUMANIORA, 2025)
This article deals with the investigation of undoing gender in Dear Me Beauty advertised in Instagram post. The promotions of makeup products using male models are identified as an action to break the stereotypes of beauty products by “undoing” dominant notions of personhood commonly done by woman. The data were collected from Instagram which were posted in 2022. This research constitutes a reconsideration of Dear Me Beauty advertisement that employs gender performativity for celebrating persistence and existence of diverse gender expression. Multimodal Discourse Analysis combining Systemic Functional Linguistics by Halliday (1994), Visual Grammar by Kress & van Leeuwen (2006), and a concept of   Gender by Butler (2004) were used  to show how the interplay between semiotic modes to construe meaning. There are four images and 26 clauses selected from the post. The result of the study shows the visual and linguistics analysis of Dear Me Beauty celebrates gender diversity but remains to focus on target market as the target consumers.